The Correlation between EFL Students’ Listening Anxieties with Listening Self-Efficacy in Listening Class - Faidhur Rahmat; Aryuliva Adnan; Leni Marlina (Journal of English Language Teaching, 2020)
Self-efficacy is necessary for EFL student in controlling their own motivation, behavior, and social environments toward their language learning. Anxiety obstructs the student in improving their language skill in language learning. This research deals with the correlation between self-efficacy and listening anxiety experienced by EFL college students at English Department, Universitas Negeri Padang. The purpose of this research is to investigate the students’ self-efficacy and whether it is in correlation with their listening anxiety. The population of the research is obtained from all of the 2019 students (the second year students) who have already have taken Basic Listening course in their first year of study. This study is conducted in correlational research by using random sampling. The researcher collects data by using two instruments: listening self-efficacy questionnaire and listening anxiety questionnaire. The result of this study showed there are correlation between EFL students’ listening self-efficacy and their listening anxiety.  The correlation between the two aspects is low and it is in the same direction. On the other hand, students’ speaking anxiety and self-efficacy stand in the medium level. They are not high and also not low.